The grass is always greener: a critical look at the lessons and challenges of acupuncture education in America - Hou, Zhitao; Sun, Zhongren (Frontiers in Medicine, 2025)
Acupuncture education forms the foundation for the growth and dissemination of acupuncture in the United States, reflecting its journey toward integration and diversity. Over the past half-century, since the “acupuncture boom,” the U.S. has developed one of the most comprehensive and large-scale acupuncture education systems outside of China. Among these, the diverse schools of acupuncture exemplify the pluralistic evolution of this field in America. This study reviews the formation, transmission, and establishment of various acupuncture schools in the U.S., analyzing their development through the lenses of constructivist and structuralist teaching theories. It identifies key challenges, including fragmented academic frameworks, insufficient theoretical grounding, and a lack of cultural integration. To address these issues, the paper proposes strategies for educational reform, curriculum design, textbook development, and cultural exchange, offering insights to guide the global expansion of acupuncture education and Traditional Chinese Medicine.